HUBUNGAN ASUPAN NATRIUM DENGAN TEKANAN DARAH MAHASISWA KAMPUS III POLITEKNIK KESEHATAN KEMENKES SEMARANG - Putri Astriandini; Setyo Prihatin; Mohammad Jaelani (Poltekkes Kemenkes Semarang, 2015)
Background : At present the problem of hypertension does not only occur in elderly people, but also has a lot happening in adolescence and early adulthood. Many factors affect blood pressure. One of them is sodium intake. The results of preliminary observations to 10 students, on average students consumed sodium from food and instant drinks of 743.81 mg / day. This does not include the source of sodium from food consumed daily.Objective : The purpose of this study is to determine the relationship between sodium intake and blood pressure in students of Campus III Poltekkes Semarang.Method : This study included the field of clinical nutrition with a cross sectional approach. The research sample was 34-21 year old students totaling 34 people. Data collection includes systolic, diastolic and sodium intake. To find out the relationship between variables used Rank Spearman test with 95% confidence level.Result : The test results showed an average systolic blood pressure of 111.71 mmHg, diastolic blood pressure of 75.5 mmHg and sodium intake of 1632.8 mg / day. Students with abnormal systolic blood pressure were 20.6%, abnormal diastolic blood pressure was 20.6% and consumption of sodium 001500 mg / day was 79.6%.Conclution : The results of the analysis show that there is a relationship between sodium intake and systolic blood pressure (p = 0.043) and r = 0.348. There is a relationship between sodium intake and diastolic blood pressure (p = 0.002) and r = 0.518. It is recommended to do further research regarding the relationship between sodium intake and blood pressure and other factors that affect blood pressure.